DESIGN AND SIMULATION OF FAST DISPATCHING HEXAGONAL CLAMP BASED ON ANSYS/LSDYNA - LIU GuoPing; FANG Bin; WANG WeiQiang; HU RongHua (Jixie qiangdu)
Currently,the production process of firecrackers is very complex. Each station is fragmented and is far away.Firecrackers production needs long-distance transport for many times by human. Consequently,the production efficiency is low.In this paper,a new fast reusable hexagonal dispatching clamp is designed and the reliable clamping and shaping effect of new fast hexagonal dispatching clamp to hexagonal firecrackers cake is simulated by using explicit dynamic procedure of ANSYS / LSDYNA,the ideal of perfectly clamping and shaping is demonstrated by using the new fast dispatching hexagonal clamp to hexagonal firecrackers cake. It provides a feasible method and has important reference for multi station automatic integrated production of fireworks.